Engineered multifunctional transforming growth factor-β type II receptor ectodomain fusions for oncology applications - Lenferink, Anne E. G.; Zwaagstra, John C.; Baardsnes, Jason; Delafosse, Laurence; Parat, Marie; Iqbal, Umar; Lessard, Etienne; Haqqani, Arsalan S.; Jezierski, Anna; Abu-Thuraia, Afnan; Tabariès, Sébastien; Siegel, Peter M.; et al. (Frontiers in Oncology, 2025)
IntroductionThe transforming growth factor-β (TGF-β) superfamily consists of a large number of evolutionarily conserved and structurally related polypeptide growth factors. TGF-β elicits a wide range of context-dependent cellular responses that play important roles in the maintenance of normal physiological processes and is implicated in various pathologies, including cancer. In healthy cells and in the early stages of cancer development, TGF-β acts as a tumor suppressor by inducing cell cycle arrest and apoptosis. However, in late-stage cancer cells, TGF-β can promote tumorigenesis, including epithelial-mesenchymal transition (EMT), metastasis and chemoresistance.MethodsThe dual-function and pleiotropic nature of TGF-β makes therapeutic targeting of this molecule a significant challenge. In this report, we describe the design and development of a novel class of TGF-β-targeting therapeutics in which the TGF-β type II receptor ectodomain (TβRII-ED) can be fused to an intact antibody, such as Cetuximab, or an antibody Fc fragment, without compromising the TβRII-ED or antibody function. Results and DiscussionAs such, we constructed and characterized specific TβRII-ED-Fc fusions that act as efficient TGF-β ligand traps with picomolar in vitro neutralizing potencies against TGF-β1 and TGF-β3 isoforms, but not TGF-β2. We further demonstrate that TβRII-ED-Fc is a versatile ligand-trapping module that, when combined with a specific targeting moiety, can lead to powerful anticancer biotherapeutics targeted to and retained at the tumor site, by efficiently neutralizing the tumor-promoting activities of TGF-β in vivo.